Determination of the prevalence of drug misuse by meconium analysis. Issue 4 (21st June 2006) - Williamson, S; Jackson, L; Skeoch, C; Azzim, G; Anderson, R
Abstract : In a pilot study to determine the local prevalence of maternal drug misuse, meconium from 400 infants was analysed for metabolites of eight controlled drugs. Cannabinoids were found in 13.25%, cocaine in 2.75%, and amphetamine in 1.75%. The prevalence of opiate and benzodiazepine misuse was masked by the presence of prescribed drugs so was undeterminable.